Effects of Light Intensity and Photoperiod on the Feeding Behavior of Rainbow Trout Oncorhynchus mykiss (Walbaum, 1792) - Xiao Liu; Liuyi Huang; Qiqing Liu; Run Wang; Bo Liu; Zhaomin Li; Yacai Song; Ziyi Huang (Fishes, 2026)
Light is a critical factor influencing fish behavior, yet the low-light conditions in deep-sea cages may impair feeding in visual species like rainbow trout Oncorhynchus mykiss (Walbaum, 1792). This study investigated the effects of light intensity and photoperiod on the feeding behavior of rainbow trout. Using green light, a factorial design tested three light intensities (10, 100, and 1000 lx) and three photoperiods (8L:16D, 16L:8D, and 24L:0D), alongside a complete darkness control (0 lx and 0L:24D). Key behavioral parameters during feeding were quantified via video analysis. The results showed significant main and interactive effects of light intensity and photoperiod on feeding behaviors. Feeding activity was substantially suppressed under continuous darkness. On the initial experimental day, exploratory movement was greatest under 10 lx and 8L:16D. Following 50 days of exposure, fish in light groups exhibited more focused swimming trajectories near the feeding point, indicating behavioral adaptation and spatial learning. Correlation analyses suggested a strategic shift from broad exploration to precise, efficient localization over time. In conclusion, specific lighting conditions, notably low intensity under a regular photoperiod, promote efficient feeding behavior in rainbow trout, whereas darkness or extreme light regimens are inhibitory. These findings reveal adaptive behavioral plasticity in this species and provide a scientific basis for optimizing light management in offshore salmonid aquaculture.